A Review of Ultra-High Performance Concrete (UHPC) - Hui, Yuantao (International Journal of Natural Resources and Environmental Studies, 2025)
Ultra-high performance concrete (UHPC), as a new generation of cement-based composite, features ultra-high strength, excellent toughness, and outstanding durability, demonstrating tremendous application potential in civil engineering. This paper systematically reviews the development history, preparation technologies, performance mechanisms, engineering applications, and future trends of UHPC. By analyzing recent research achievements at home and abroad, it summarizes significant progress in material composition optimization, process improvement, performance enhancement, and engineering applications. Results indicate that UHPC technology is becoming increasingly mature, with expanding applications in bridges, buildings, and marine engineering. Nevertheless, further research is needed in cost control, standardization, and long-term performance evaluation. With the deepening concepts of green construction and sustainable development, UHPC is expected to play an increasingly important role in infrastructure construction.